2017
DOI: 10.1002/cbin.10744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a critical single nucleotide polymorphism on nuclear receptor PXR‐promoter function

Abstract: The Pregnane and Xenobiotic Receptor (PXR; NR1I2) is a ligand-modulated transcription factor that belongs to the nuclear receptor superfamily. It is expressed at higher levels primarily in liver and intestine as compared to the levels in several other organs. It is activated by a broad spectrum of xenobiotics and endobiotics. The primary function of PXR is to regulate the expression of drug metabolizing enzymes and transporters and prevent the accumulation of toxic chemicals in the body, thereby maintaining bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…The TT genotype of rs3814055 has previously been shown to be associated with higher induction by rifampicin of CYP3A4 avtivity in a study by Zhang[35]. A change from a C to a T allele was associated with significantly greater transcriptional activity in a study by Manjul Rana[36], which indicates that the rs3814055 C/T polymorphism has a direct effect on the transcriptional upregulation of PXR. In another study of flucloxacillin-induced hepatotoxicity, the CC genotype (rs3814055) was associated with an increased risk of hepatocyte injury in the presence of the decreased expression of CYP3A4, which may result in a higher accumulation of unmetabolized toxic drugs and lead to hepatocellular injury [13].…”
Section: Discussionmentioning
confidence: 96%
“…The TT genotype of rs3814055 has previously been shown to be associated with higher induction by rifampicin of CYP3A4 avtivity in a study by Zhang[35]. A change from a C to a T allele was associated with significantly greater transcriptional activity in a study by Manjul Rana[36], which indicates that the rs3814055 C/T polymorphism has a direct effect on the transcriptional upregulation of PXR. In another study of flucloxacillin-induced hepatotoxicity, the CC genotype (rs3814055) was associated with an increased risk of hepatocyte injury in the presence of the decreased expression of CYP3A4, which may result in a higher accumulation of unmetabolized toxic drugs and lead to hepatocellular injury [13].…”
Section: Discussionmentioning
confidence: 96%
“…PXR also plays a pivotal role in the process of certain human disorders including diabetes, cholestasis, hyperlipidemia, cancer and IBD 6 . Recently, some studies showed that activation of PXR protects against chemical-induced IBD in mice, and mutation of PXR gene is highly correlated with the susceptibility to IBD 5,7,8 . Furthermore, studies on the pathogenesis of IBD have revealed that some specific single-nucleotide polymorphisms in PXR gene have been associated with a reduction of PXR expression and an increase of human IBD susceptibility 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies showed that activation of PXR protects against chemical-induced IBD in mice, and mutation of PXR gene is highly correlated with the susceptibility to IBD 5,7,8 . Furthermore, studies on the pathogenesis of IBD have revealed that some specific single-nucleotide polymorphisms in PXR gene have been associated with a reduction of PXR expression and an increase of human IBD susceptibility 8 . Additionally, a reciprocal crosstalk has been described between nuclear factor-kappa B (NF-κB) and PXR 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because gene mutations in COL6A1 , COL6A2 and COL6A3 have been shown to result in muscular dystrophy, which indicated that collagen VI is particularly necessary for the vitality of skeletal muscle. Further, the article by Lampe AK et al [8] about collagen VI related muscle disorders describes that mutations in the collagen genes ( COL6A1 , COL6A2 , and COL6A3 ) can give rise to Bethlem myopathy (BM) and Ullrich congenital muscular dystrophy (UCMD). The recessive COL6A3 mutations (p.R3043H and p.P3082R) can cause neurological disorder early-onset isolated dystonia [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…COL6A3 , encoding the a3(VI) chain, contains two C terminal Von Willebrand factor type A-like domains, subdomains similar to type III fibronectin repeats, and Kunitz protease inhibitors as well as 6–10 N-terminal Von Willebrand factor type A-like domains, thus contributing to most of the amino-terminal globular domain of the collagen VI heterotrimer. This protein is an extracellular matrix protein found in most tissues and its absence or aberrant formation can result in many diseases, such as Congenital Muscular Dystrophies (CMDs) [8].…”
Section: Introductionmentioning
confidence: 99%